Preliminary Observations of the Abyssal Megafauna of Kiribati - Simon-Lledó, Erik; Thompson, Samuel; Yool, Andrew; Flynn, Adrian; Pomee, Christina; Parianos, John; Jones, Daniel O. B. (Frontiers in Marine Science, 2019)
We report on preliminary observations of the abyssal megafauna communities in the exclusive economic zone of Kiribati, a huge abyssal area with few previous studies. These observations also provide useful context for marine minerals exploration within the EEZ and for the neighbouring Clarion Clipperton Zone (CCZ), where deep-sea mining operations are planned. Seafloor images collected during seabed mining exploration were used to characterise megafaunal communities (fauna > 1 cm) in three abyssal plain areas in the eastern Kiribati EEZ (study area extending from 1-5°N and 173-156°W). Additionally, hydrographic features in each of the survey locations were inferred by reference to near-seabed current flows modelled using open-sourced oceanographic data. The images showed a dominance of foraminiferal organisms. Metazoan communities were high in morphospecies richness but had low density. These general patterns were comparable to abyssal megabenthic communities in the CCZ. There was evidence of spatial variation between the assemblages in Kiribati, but there was a relatively large pool of shared morphospecies across the entire study area. Low metazoan density constrained detailed assessment of spatial variation and diversity at local scales. This finding is instructive of the levels of sampling effort required to determine spatial patterns in low density abyssal communities. The results of this study are preliminary observations that will be useful to guide future biological survey design and marine spatial planning strategies.